2016
DOI: 10.1007/s10934-016-0186-z
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of mesostructured NH2-MIL-101(Cr) and kinetic and thermodynamic study in tetracycline aqueous solutions

Abstract: In this paper, metal-organic framework NH 2 -MIL-101(Cr) was prepared and used as an adsorbent for removing tetracycline from aqueous system. The results showed that NH 2 -MIL-101(Cr) had the better adsorption property for tetracycline. The adsorption capacities for tetracycline reached 36.15 and 48.80 % in 10 and 240 min, respectively. Additionally, the study of adsorption kinetics and thermodynamic theories showed that the adsorption kinetics and thermodynamic datum of tetracycline were adapted to the pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…The last two vibrations happen due to the asymmetric and symmetric N-H stretching of the amino group whereas the lower end band is caused by C-N stretching vibration. All signals are in accordance to values reported in literature [39,48].…”
Section: Ftirsupporting
confidence: 90%
See 1 more Smart Citation
“…The last two vibrations happen due to the asymmetric and symmetric N-H stretching of the amino group whereas the lower end band is caused by C-N stretching vibration. All signals are in accordance to values reported in literature [39,48].…”
Section: Ftirsupporting
confidence: 90%
“…As for MOFs, generally, there are three distinct weight loss steps. The first step between 30 • C and 150 • C refers to the loss of moisture adsorbed from air and residual solvents used for washing (EtOH and DMF) from the large cages [48]. Next, strongly adsorbed water molecules are removed from the middle sized cages from • C to 370 • C. Above 370 • C, compounds such as -OH and other coordinated groups are eliminated simultaneously causing MIL-101 framework decomposition [38,39,51,52].…”
Section: Tgamentioning
confidence: 99%
“…The XRD patterns of the two MOFs (Fig. 2) indicate the typical main diffraction peaks of the structure and are consistent with the data presented in the literatures [34,35]. The characteristic diffraction peaks of the as-prepared NH 2 -MIL-88B(Fe) appeared at approximately 9.2°, 10.2°, (Fig.…”
Section: Characterizations Of Nh 2 -Fe-milssupporting
confidence: 88%
“…Tian et al used functional MOFs to adsorb tetracycline in water and found that the adsorption process conformed to pseudo-second-order kinetics. 15 Jhung et al used MOFs to adsorb benzene in water and the equilibrium adsorption capacity was 16.7 mmol g À1 , 16 which was higher than that of AC at 8.0 mmol g À1 . Hasan et al used MOFs to adsorb naproxen and clobric acid in water, 17 nding that they had higher adsorption capacities and adsorption rate constants than AC.…”
Section: Introductionmentioning
confidence: 99%